Prevalence of Enterotoxigenic Bacteroides Fragilis in Stool Specimens Collected from Children Less Than 5 Years Of Age in Iraq - Jasim, Dhyiaa Ahmed; Melconian, Alice (Iraqi Journal of Science, 2020)
Although Bacteroides fragilis is a bacterium present within gut microbiota, the toxin producer strain, known as enterotoxigenic B. fragilis (ETBF), is associated with diarrhea in children less than 5 years of age. This study includes 69 diarrheal and 29 non-diarrheal (control) samples collected from children less than 5 years old. DNA was extracted directly from stool specimens and directed to conventional PCR targeting beta-isopropylmalate dehydrogenase (leuB) gene, used for detection of B. fragilis, and Bacteroides fragilis toxin (bft) gene, used for the detection of ETBF. The results showed that the prevalence of leuB gene was 78 (79.6%) including 56 (81.2%) in diarrheal and 22 (75.9%) in non-diarrheal subjects, while that of bft gene was only 3 (3.1%) including 2 (2.9%) in diarrheal and 1 (3.4%) in non-diarrheal subjects. Based on sequencing of bft-positive specimens, both bft-1 and bft-2 isoforms were represented in diarrheal specimens, whereas only bft-1 was found in the control specimens. In conclusion, this study examined for the first time the leuB and bft gene in a specimen of Iraqi children with diarrhea and showed no significant differences between diarrheal and control groups in both genes.